Copper-Catalyzed Enantioconvergent Radical Suzuki–Miyaura C(sp3)–C(sp2) Cross-Coupling - Jiang, Sheng-Peng; Dong, Xiao-Yang; Gu, Qiang-Shuai; Ye, Liu; Li, Zhong-Liang; Liu, Xin-Yuan (Journal of the American Chemical Society, 2020)
A copper-catalyzed enantioconvergent Suzuki–Miyaura C(sp3)–C(sp2) cross-coupling of various racemic alkyl halides with organoboronate esters has been established in high enantioselectivity. Critical to the success is the use of a chiral cinchona alkaloid-derived N,N,P-ligand for not only enhancing the reducing capability of copper catalyst to favor a stereoablative radical pathway over a stereospecific SN2-type process but also providing an ideal chiral environment to achieve the challenging enantiocontrol over the highly reactive radical species. The reaction has a broad scope with respect to both coupling partners, covering aryl- and heteroarylboronate esters, as well as benzyl-, heterobenzyl-, and propargyl bromides and chlorides with good functional group compatibility. Thus, it provides expedient access toward a range of useful enantioenriched skeletons featuring chiral tertiary benzylic stereocenters.